Novel Nano Calcium Fluoride Remineralizing and Antibacterial Dental Composites. (October 2021) - Mitwalli, Heba; AlSahafi, Rashed; Albeshir, Ebtehal G.; Dai, Quan; Sun, Jirun; Oates, Thomas W.; Melo, Mary Anne S.; Xu, Hockin H.K.; Weir, Michael D.
Abstract: Objective: Composites with remineralizing and antibacterial properties are favorable for caries inhibition. The objectives of this study were to develop a new bioactive nanocomposite with remineralizing and antibiofilm properties by incorporating dimethylaminohexadecyl methacrylate (DMAHDM) and nano-calcium fluoride (nCaF2 ). Methods: nCaF2 was produced via a spray-drying method and integrated at 15% mass fraction into composite. DMAHDM was added at 3% mass fraction. Mechanical properties and F and Ca ion releases were assessed. Colony-forming units (CFU), lactic acid and metabolic activity of biofilms on composites were performed. Results: The new composites had flexural strengths of (95.28±6.32) MPa and (125.93±7.49) MPa, which were within the ISO recommendations. Biofilm CFU were reduced by 3–4 log ( p <0.05). The composites achieved high F releases of (0.89±0.01) mmol/L and (0.44±0.01) mmol/L, and Ca releases of (1.46±0.05) mmol/L and (0.54±0.005) mmol/L. Conclusions: New nanocomposites were developed with good mechanical properties, potent antibacterial activity against salivary biofilms, and high F and Ca ion releases with potential for remineralization. Clinical Significance: Novel nanocomposites using nCaF2 and DMAHDM were developed with potent antibacterial and remineralizing effects and high F and Ca ion releases. They are promising to inhibit recurrent caries, promote remineralization, and possess long-term sustainability.